Challenges and responses : Six studies in Missionary Opportunity - Warren, Max; Robinson, Gnana, 1935-; United Theological College (Bangalore, India); Asian Trading Corporation (Bangalore : Published on the occasion of the ninetieth year celebration of the United Theological College by Asian Trading Corp., 2000)
Contributed articles.
"UTC jubilee volume"--Cover.
Includes bibliographical references and index.
Keywords: Theology -- Study and teaching; Mission of the church